Clinical Outcomes After Reverse Shoulder Arthroplasty With and Without Subscapularis Repair: The Importance of Considering Glenosphere Lateralization. Issue 5 (1st March 2018) - Werner, Brian C.; Wong, Alexandra C.; Mahony, Gregory T.; Craig, Edward V.; Dines, David M.; Warren, Russell F.; Gulotta, Lawrence V.
Abstract : Introduction: Recent biomechanical data suggests that repairing the subscapularis during reverse shoulder arthroplasty (RSA) can increase the force required by the posterior rotator cuff and deltoid to elevate the arm. Methods: We retrospectively studied patients who underwent primary RSA and had baseline and minimum 2-year postoperative American Shoulder and Elbow Surgeons (ASES) shoulder scores, stratified them according to subscapularis management, then subgrouped them according to lateralization of the glenosphere component. Results: Patients with subscapularis repair and a lateralized glenosphere had significantly less improvement in ASES scores than did those without lateralization ( P = 0.016) and patients without subscapularis repair ( P = 0.006). Individually, subscapularis management ( P = 0.163) and glenosphere lateralization ( P = 0.847) had no significant effect on the change in ASES score but in combination did have a significant effect on the change in ASES score ( P = 0.002). Discussion: The combination of subscapularis repair and glenosphere implant lateralization in RSA translates to significantly less clinical improvement. Conclusions: Patients who underwent both subscapularis repair and glenosphere lateralization had significantly less improvement in ASES scores. Level of Evidence: Level III